Computer-supported collaborative knowledge construction learning environment / Siti Soraya Abdul Rahman - Siti Soraya, Abdul Rahman (2002)
The current interest in the use of information communication technology (ICT) has made it feasible to consider constructivism principles within the context of the technology-mediated higher education. This is primarily due to advances in ICT resulting in an effective means to implement constructivism principles, which would be difficult to accomplish with other media. In this development, computers play an important role. Computer Supported Collaborative Learning (CSCL), especially, offers promising innovations and tools for restructuring teaching-learning processes to prepare students for education today. An attempt is made in this thesis to explore the current pedagogical perspectives of learning on educational practices particularly the constructivism and collaborative learning principles. The combination of these principles leads the development of higher education towards the achievement of their main current goals hence prepares individuals for a lifelong learning. This thesis describes and exemplifies a theoretically based approach to the design of collaborative knowledge construction learning environment. First, the detailed studies of learning theories on educational practices particularly cognitive contructivism, social constructivism and collaborative learning was disposed by introducing a model, named Collaborative Knowledge Construction process model (COKC) to direct student learning through collaborative knowledge construction activities at the levels of Articulation, Comparison, Argumentation, Clarification, Negotiation, and Integration. Second, a conceptual framework for the application of Knowledge Construction Space (KC-Space) developed from this model has also been proposed. Third, this framework has been used as a basis for the design and development of KC Space Space learning environment. Next the KC-Space has been evaluated and research findings from the pilot study are reported to be satisfactory. Finally, it highlights the essential contributions of this research and outlines promising future research directions.